2013
DOI: 10.1038/ncb2679
|View full text |Cite
|
Sign up to set email alerts
|

Spatial regulation of VEGF receptor endocytosis in angiogenesis

Abstract: Activities as diverse as migration, proliferation and patterning occur simultaneously and in a coordinated fashion during tissue morphogenesis. In the growing vasculature, the formation of motile, invasive and filopodia-carrying endothelial sprouts is balanced with the stabilisation of blood-transporting vessels. Here, we show that sprouting endothelial cells in the retina have high rates of VEGF uptake, VEGF receptor endocytosis and turnover. These internalisation processes are opposed by atypical protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
241
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(263 citation statements)
references
References 53 publications
19
241
1
2
Order By: Relevance
“…The cell surface pool of VEGFR2 is homeostatically replenished by both de novo protein synthesis induced by VEGF signaling itself (Gampel et al, 2006;Domingues et al, 2011) and by recycling of residual intact receptor. The process of transport of VEGFR2 to the membrane is essential for sprouting endothelial cells at the tips of growing vessels, where a constant supply of VEGFR2 is needed for vessel outgrowth (Nakayama et al, 2013). In the present study, we demonstrated that the molecular motor kinesin KIF13B is required for the transport and endothelial cell surface positioning of VEGFR2, and hence it was essential for angiogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…The cell surface pool of VEGFR2 is homeostatically replenished by both de novo protein synthesis induced by VEGF signaling itself (Gampel et al, 2006;Domingues et al, 2011) and by recycling of residual intact receptor. The process of transport of VEGFR2 to the membrane is essential for sprouting endothelial cells at the tips of growing vessels, where a constant supply of VEGFR2 is needed for vessel outgrowth (Nakayama et al, 2013). In the present study, we demonstrated that the molecular motor kinesin KIF13B is required for the transport and endothelial cell surface positioning of VEGFR2, and hence it was essential for angiogenesis.…”
Section: Discussionsupporting
confidence: 55%
“…Recent reports showing that the Wnt noncanonical pathway activated by Wnt5a, as well as the Par/aPKC PCP complex contribute in vivo to retinal vessel maturation are in line with our proposition. 39,40 In conclusion, we propose that Wnt factors control BBB integrity through activation of multiple signaling pathways, including the canonical Wnt/b-catenin pathway 12,13,15 and the Wnt/Par/aPKC PCP pathway (this study). Further investigations will aim at assessing whether additional pathways, such as the Wnt/calcium pathway, may also contribute to BBB integrity.…”
Section: Discussionmentioning
confidence: 84%
“…Of these, VEGFs and their receptors (Flk and Flt) are considered to be master determinants of vasculogenesis and angiogenesis, as together they regulate the survival, differentiation, proliferation, morphogenesis and migration of ECs (Gentile et al, 2013;Hang et al, 2013;Nakayama et al, 2013). Given their crucial role in vascular development, genes encoding VEGFs have been widely used as therapeutic pro-angiogenic factors in clinical trials or to regulate vascular differentiation and morphogenesis to create vascular network structures in vitro (Hanjaya-Putra et al, 2010;Yee et al, 2011).…”
Section: Growth Factors Are Crucial During Vascular Formationmentioning
confidence: 99%